Методологія побудови сценаріїв розвитку складних соціальних систем із використанням морфолоічного та SWOT-анализу. Частина 1 - Pereverza, K. V. (The National Technical University of Ukraine "Igor Sikorsky Kyiv Polytechnic Institute", 2012)
In this part of the article a methodology of scenario development for complex social systems ia presented. Proposed methodology consists of 9 stages, for each of which the methods, the nature of the input and output of information, practical advice are described. The procedures of obtaining of expert information on the key variables of the system, driving forces, the states of the driving forces that affect on it and future states of the driving forces of their consistency are described. For selecting key variables of the system the approach on the basis of SWOT-analysis is proposed. To generate many of the scenarios it is proposed to use a morphological analysis. A scenario space, built with the help of morphological analysis, is reduced in the result of the analysis of the consistency of the states of the driving forces. For the analysis of the scenario space in the general form there are several approaches in the article, but this task remains open and promising for further investigation.